Quranic Values In Embedded Parenting In Improving The Quality Of Children's Education: Nilai-Nilai Al-Qur’an Pada Pengasuhan Melekat Dalam Peningkatan Kualitas Pendidikan Anak - Albarra, Albarra; Nawawi , Adlan; Tasbih, Agus (Civilization Research: Journal of Islamic Studies, 2025)
This study aims to analyze the values of the Quran on inherent parenting in improving the quality of children's education. The research method used is library research, with data collection from various literatures such as books, journals, magazines, and related documentation. The results showed that embedded parenting, which emphasizes emotional closeness and consistent support from parents, proved effective in improving the quality of children's education. Attachment parenting contributes to children's cognitive, social and emotional development as shown through better academic achievement, improved social skills and better emotional stability. The importance of Qur'anic Values in embedded parenting such as tawhid, respect for parents, responsibility, discipline and social care contribute to children's affective, cognitive and psychomotor development. Parenting that reinforces these values supports the formation of quality character. By strengthening embedded parenting and integrating Qur'anic values, we can build a quality next generation and improve the future of children's education in Indonesia.